MORAL AND PSYCHOLOGICAL PREPAREDNESS IN THE PHYSICAL TRAINING OF MILITARY PERSONNEL: IMPORTANCE AND METHODOLOGICAL APPROACHES - Lieutenant Colonel Davlat Eldorovich Vakhobov (Journals Park Publishing, 2025)
This article examines the crucial role of moral and psychological preparedness in the physical training of military personnel. In the contemporary security landscape characterized by complex military-political threats and global tensions, soldiers are required not only to possess strong physical capabilities but also high levels of moral and psychological resilience. The research identifies the significant impact of moral-psychological readiness on operational efficiency, stress management, and decision-making under extreme conditions. Methodologically, the study is based on a mixed approach, integrating a review of international scientific literature, statistical analysis of surveys conducted among military personnel, and comparative studies. The findings reveal that military units implementing comprehensive moral-psychological training experience a marked improvement in combat performance, group cohesion, and psychological stability. Based on the results, specific recommendations are proposed to institutionalize moral-psychological training and innovate military educational programs. The study underscores the necessity of treating moral and psychological preparedness as a fundamental pillar of military effectiveness in modern warfare.
Keywords: Moral preparedness, psychological resilience, military training, combat readiness, stress management, military pedagogy, military psychology, operational efficiency, resilience training, ethical leadership.